Physical education: a reflection on subject status, the critical, and the wellbeing agenda - Fitzpatrick, Katie (Sport, education and society, 2023)
This article is based on a lecture given as a result of the Catherine D. Ennis Outstanding Scholar Award 2021, presented by the American Educational Research Association (AERA) special interest group for Research on Learning and Instruction in Physical Education. It is a reflection on the field of physical education, beginning with an argument that issues of low status continue to impact practices, even while the wellbeing agenda intensifies. I then reflect on research in the field of physical education and argue that inquiries can be thought of as broadly belonging to one or more of three different areas: intervention research, pedagogical research and critical research. I argue that these areas have different agendas and different ontologies, which produce particular responses to the issues of low status and the wellbeing agenda. I draw on some of my own current work in mental health education to argue that we need to keep an educative approach to the fore if we want to continue to contest the low status of physical education, and respond to the wellbeing agenda.